Sediment Flushing using Tipping Flush Gate in an Open Storm Concrete Drain – A Case Study in Nibong Tebal, Penang, Malaysia - Bong, Charles Hin Joo; Tze, Liang Lau; Aminuddin, Bin Ab Ghani (2013)
This paper presents a case study of using a tipping flush gate for sediment flushing in an open concrete storm drain. The study was conducted in an open concrete storm drain located in Taman Pekaka, Nibong Tebal, Penang, Malaysia with the objectives to study the scouring effect of flushing on sediment in the drain and also the feasibility to use tipping flush gate in an open drain system. The monitoring period was from 14 November 2012 to 15 March 2013. Sediment profile was measured after each operation of the gate or rainfall event using a simple stick. Results from the study shows that the flush gate is efficient in sediment removal with longer flushing operation time than the study on Hydrass gate in closed sewer system. However, problems such as debris caught at the gate, accumulation of debris behind the gate and water ponding causing mosquito breeding need to be address before the gate could be implemented for an open drain system.